Immunological responses toward caseous lymphadenitis recombinant vaccine incorporated with different adjuvants - Md Nor, Roslindawani (2018)
Caseous lymphadenitis (CLA) is a chronic disease of sheep and goats worldwide. It is caused by a bacterium known as Corynebacterium pseudotuberculosis leading to considerable economic losses. CLA was rarely reported in Malaysia until recently, following the importation of goats. Control of CLA via vaccination has not been recommended so far. This was due to the uncertain efficacy of the only commercially available vaccine against CLA, the Glanvac6TM vaccine. In fact, earlier study has revealed that the Glanvac6 vaccine failed to provide significant protection to goats following challenged by live wild-strain of C. pseudotuberculosis. Recombinant vaccines encoding the 31kDA and 40kDa outer membrane proteins were subsequently developed but proved to be ineffective in protecting goats. This study was conducted to determine the effect of different concentrations of adjuvants; the palm-based oil and the lipopolysaccharide (LPS) of Pasteurella multocida B:2 on the ability of a newly developed recombinant CLA vaccine (pET32/LIC-Omp40) to stimulate immune response, hence determined the best concentration of the adjuvant for CLA vaccine preparation. Three different concentrations of each adjuvant were used; the 3%, 5% and 7% of palm-based oil or LPS and were vaccinated into rat model at weeks 0 and 2. The immunoglobulin and cell-mediated immune responses were measured weekly for a period of 10 weeks. The results revealed that rats vaccinated with 3% palm oil adjuvanted recombinant vaccine showed significantly (p<0.05) highest antibody levels. Other groups (the 5% and 7% palm oil and the 3%, 5% and 7% LPS) showed no significant (p>0.05) different in the IgG levels compared with the vaccine without adjuvant. Similarly, the 3% palm oil produced significantly (p<0.05) highest percentage of CD4+ and CD8+ cells compared to other groups. Hence, it is concluded that the best concentration and adjuvant for the CLA recombinant vaccine is the 3% of palm oil. Then, the efficacy of the newly developed recombinant CLA vaccine containing 3% palm oil adjuvant was compared with the vaccine containing 10% Freund’s incomplete adjuvant (FIA) as adjuvant in goats. Nine adult female goats with no history of vaccination against CLA were selected and divided into 3 equal groups consisting of 3 goats per group. Goats of group 1 were vaccinated intramuscularly with the recombinant vaccine containing 10% FIA, Group 2 with the same vaccine containing 3% palm oil as adjuvant and Group 3 with PBS. Booster dose of the respective vaccine was administered two weeks after the first vaccination. All goats were challenged subcutaneously with 1ml of 109 cfu/ml of live C. pseudotuberculosis at week 4. Serum and whole blood sample were collected from all goats before vaccination and at weekly intervals post-vaccination throughout the 12-week study period to determine the immunoglobulin status via enzyme-linked immunosorbent assay (ELISA) and the cell-mediated immunity status via immunofluorescent assay. At the end of the study, all goats were killed by exsanguinations before organ and lymph node samples were collected for bacterial isolation and lesion scoring. The results revealed that both palm oil adjuvanted and the Freund’s adjuvanted recombinant CLA vaccines produced significantly high (p<0.05) antibody levels compared to the control throughout the 12-week study period. Following challenged with live C. pseudotuberculosis, the antibody levels of Group 1 increased insignificantly (p>0.05) but Group 2 increased significantly (p<0.05) when compared to the control group. Similarly, Groups 1 and 2 showed significantly (p<0.05) higher percentage of CD4+ compared to the control until week 3 but started to decrease from week 4 until the end of the study period. In contrast, the percentage of CD8+ remained significantly (p<0.05) high throughout the entire study period. Following challenged, C. pseudotuberculosis was successfully isolated from all groups of goats. In fact, goats of Groups 1 and 2 showed most severe lesions. This was due to the fact that the adjuvanted vaccines stimulated significant (p<0.05) humoral and cell-mediated immune responses but lasted for a short period of time. It requires consistent booster to maintain the immune response.